Poziom rozwoju somatycznego i funkcjonalnego mężczyzn i kobiet po 60. roku życia = The level of somatic and functional development in men and women over 60 - Asienkiewicz, Ryszard; Biczysko, Grażyna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the study was to show morpho-functional diversity in groups of men and women between the ages of 60 and 85. The authors gathered the material among 111 women and 27 men representing Universities of the Third Age in the Lubuskie Voivodeship and participating in the "Active Seniors" Project (Projekt "Aktywny Senior") in 2017. Martin`s technique was used to measure the length and breadth of their body parts, circuits, thickness of skin- and fat-folds, and body mass. The level of functional fitness in older adults was evaluated through the six tests of the "Fullerton Functional Fitness Test".
Keywords: rozwój fizyczny; rozwój funkcjonalny; seniorzy; charakterystyka porównawcza; physical development; functional development; seniors; comparative characteristics